A simulation method for determining the optical response of highly complex photonic structures of biological origin - Dolinko, Andrés Ezequiel (2013)
We present a method based on a time domain simulation of wave propagation that allows studying the optical response of a broad range of dielectric photonic structures. This method is particularly suitable for dealing with complex biological structures. One of the main features of the proposed approach is the simple and intuitive way of defining the setup and the photonic structure to be simulated, which can be done by feeding the simulation with a digital image of the structure. We also develop a set of techniques to process the behavior of the evolving waves within the simulation. These techniques include a direction filter, that permits decoupling of waves travelling simultaneously in different directions, a dynamic differential absorber, to cancel the waves reflected at the edges of the simulation space, a multi-frequency excitation scheme based on a filter that allows decoupling waves of different wavelengths travelling simultaneously, and a near-to-far-field approach to evaluate the resulting wavefield outside the simulation domain. We validate the code and, as an example, apply it to the complex structure found in a microorganism called Diachea leucopoda, which exhibits a multicolor iridescent appearance.